Xanthine – A promising organic material for the development of nanostructured anti-reflective layers - Gärtner, Anne; Seifert, Tina; Rickelt, Friedrich; Schulz, Ulrike; Tünnermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2021)
Anti-reflective (AR) coatings are indispensable for an excellent imaging of optical systems. Common AR coating systems consist of layer stacks of alternating low and high refractive index materials with the residual reflection depending mainly on the low refractive index (LRI) of the last layer relative to air. However, conventional LRI materials are limited to SiO2 (n = 1,46 at 532 nm) and MgF2 (n = 1,38 at 532 nm). Nanostructures with an adjustable effective LRI in the range of 1.07 to 1.25 are an attractive alternative to these materials. Integrated as the last layer in the stack system, these structures significantly improve the optical performance compared to a conventional interference coating system, as a broadband AR coating can be realized. At the Fraunhofer Institute IOF in Jena, self-assembling AR nanostructures are already successfully developed using a conventional plasma-ion-assisted-deposition (Plasma-IAD) technology. Thereby organic material is deposited on the substrate via thermal evaporation and subsequently plasma-assisted self-assembling nanostructures are formed. Melamine and Uracil are already used as organic material. In this talk, we want to introduce Xanthine, another organic material that is also highly promising for the generation of nanostructures. We will demonstrate the formation of its nanostructures during plasma etching and investigate their optical performance for the use in an AR layer system.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Anti-reflective; Nanostructures; Plasma-IAD; Xanthine